Spatial patterns of the Argentine hake Merluccius hubbsi and oceanographic processes in a semi-enclosed Patagonian ecosystem - Ocampo Reinaldo, Matías (2013)
Time-series of fishing position, landings, satellite-derived sea-surface temperature and chlorophyll a concentrations were used to relate the spatial-temporal distribution of the Argentine hake Merluccius hubbsi with seasonal oceanographic processes in San Matías Gulf. Also, the seasonal effect of fishing on the hake population structure was analysed. During summer the fleet was concentrated over the area of the frontal system, obtaining the best catch-per-unit-effort (CPUE) of hake in relatively deep waters. In autumn, the dispersion of the fleet due to a reduction in CPUE coincided with the dissipation of the front, suggesting that the distribution and shoaling of the Argentine hake is associated with seasonal thermal structures. In spring, the thermal structure of the waters and the chlorophyll a blooms seem to modulate the timing of spawning of hake, which occurs mainly in October-November. In addition, the fleet captured a higher proportion of females in the gonadal recovery stage during warm months (November-April). While winter catches (May-October) consisted mainly of males, the intense summer fishing may result in a high impact on the female population. This information is relevant to design of spatial management tools intended to provide biological sustainability to the hake fishery.